The safety design methodology of beams of hyperstatic bar structures - Kliukas, R.; Kudzys, Al.; Kudzys, An. (Видавництво Національного університету «Львівська політехніка», 2007)
An assessment of structural and technological features in the design methodology of hyperstatic precast reinforced concrete and composite steel-concrete structures is discussed. Permanent and variable service, snow and wind loads of buildings and their extreme values are analysed. Two loading cases of precast reinforced concrete and composite steel-concrete continuous and sway frame beams as propped and unpropped members are considered. A limit state verification of hyperstatic beams by the partial factor and probability-based methods is presented. It is recommended to calculate a long-term survival probability of beams by the analytical method of transformed conditional probabilities.